Effect of green garlic/cucumber crop rotation for 3 years on the dynamics of soil properties and cucumber yield in Chinese anthrosol. (4th November 2019) - Ding, Haiyan; Ali, Ahmad; Cheng, Zhihui
Abstract: BACKGROUND: Long‐term drastic anthropic inputs in conventional monoculture systems cause negative plant–soil feedback that will largely affect sustainable cucumber cultivation. The inclusion of multicropping in intensive cropping systems could reduce the detrimental effects of continuous cropping obstacles. The present study investigated the dynamics of soil microbial communities, soil enzyme activities and cucumber yield under plastic tunnel cultivation for three successive growing seasons (2013, 2014 and 2015). RESULT: In the amended crop rotation system, soil pH decreased with increasing number of cropped garlic bulbs. The soil electrical conductivity significantly changed during the entire growth period and increased with increasing number of incorporated garlic bulbs. The level of soil organic matter content increased in the last year (2015). Soil catalase activity was generally induced by the treatments of 10, 15, 20 and 25 garlic bulbs, and soil invertase activity was also enhanced by all the treatments in the last year. Similarly, fungal species richness dramatically increased under these crop rotation systems. In this study, we found the highest cucumber yield under the cropping treatment of 20 garlic bulbs. CONCLUSION: The results indicate that the green garlic/cucumber cropping system is a sustainable and efficient cropping system for cucumber production and can improve the soil environment to a certain extent. © 2019 Society of Chemical Industry